Interneuron Development Is Disrupted in Preterm Brains With Diffuse White Matter Injury: Observations in Mouse and Human - Stolp, Helen B.; Fleiss, Bobbi; Arai, Yoko; Supramaniam, Veena; Vontell, Regina; Birtles, Sebastian; Yates, Abi G.; Baburamani, Ana A.; Thornton, Claire; Rutherford, Mary; Edwards, A. David; Gressens, Pierre (Frontiers in Physiology, 2019)
Preterm brain injury, occurring in approximately 30% of infants born <32 weeks gestational age, is associated with an increased risk of neurodevelopmental disorders, such as autism spectrum disorder (ASD) and attention deficit hyperactivity disorder (ADHD). The mechanism of grey matter injury in preterm born children is unclear and likely to be multifactorial, however inflammation, a high predictor of poor outcome in preterm infants, has been associated with disrupted interneuron maturation in a number of animal models. Interneurons are important for regulating normal brain development, and disruption in interneuron development, and the downstream effects of this, has been implicated in the aetiology of neurodevelopmental disorders. Here we utilise post-mortem tissue from human preterm cases with) or without diffuse white matter injury (WMI; PMA range: 23+2 to 28+1 for non-WMI group, 26+6 to 30+0 for WMI group, p=0.002), and a model of inflammation-induced preterm diffuse white matter injury (i.p. IL-1β, b.d., 10µg/kg/injection in male CD1 mice from P1-5). Data from human preterm infants show deficits in interneuron numbers in the cortex and delayed development of neuronal arbours at this early stage of development. In the mouse, significant reduction in the number of parvalbumin positive interneurons was observed from postnatal day (P) 10. This decrease in parvalbumin neuron number was largely rectified by P40, though there was a significantly smaller number of parvalbumin positive cells associated with perineuronal nets in the upper cortical layers. Together, these data suggest that inflammation in the preterm brain may be a contributor to injury of specific interneuron in the cortical grey matter. This may represent a potential target for postnatal therapy to reduce the incidence and/or severity of neurodevelopmental disorders in preterm infants.